Online Shopping: An Empirical Study of Indian Consumers - Gupta, Neha; Chandel, Jyoti; Yadav, Jyoti (International Journal of Computer Sciences and Engineering, 2014)
Online shopping - Consumers are playing an important role. In India young generations are using Internet at an increasing rate it greatly provides an emerging prospect for online retailers. There are various factors which affects Indian consumers, buying behaviour and the associations between these factors and type of online buyers, then they can further develop their marketing strategies to convert potential customers into active ones. In this study four key dimensions of online shopping as perceived by consumers in India are identified and the different demographic factors are also studied which are the primary basis of market segmentation for retailers. It was discovered that overall website quality, commitment factor, customer service and security are the four key factors which influence consumers’ perceptions of online shopping. the study revealed that the perception of online shoppers is independent of their age and gender but not independent of their education & gender and income & gender Finally, the recommendations presented in this research may help foster growth of Indian online retailing in future.